2012
DOI: 10.1309/ajcpljfss62ybawn
|View full text |Cite
|
Sign up to set email alerts
|

Cessation of Dipstick Urinalysis Reflex Testing and Physician Ordering Behavior

Abstract: The purpose of our study was to determine the effect of the elimination of laboratory-initiated reflex testing on physician ordering behavior. In 1999, we stopped laboratory-initiated reflex testing and did microscopic analysis only on physician request. The number of urinalysis dipstick tests, microscopic analysis tests, and urine cultures done during 6-month periods for the next 10 years was extracted from our laboratory information system that includes data from the middle of 1999. The number of physician c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Decreasing the cutoff to > 3 WBC/HPF increased sensitivity but still resulted in an increased number of bacteremic UTI patients with negative test results. Reflex microscopic testing after a positive dipstick test result is still a common practice [ 17 ], but our results support others who have stopped reflex microscopic examination in outpatients [ 18 , 19 ] and inpatients [ 19 ] only done by physician request. On the other hand, there might be a role for microscopic examination in those with a negative dipstick in order to increase sensitivity.…”
Section: Discussionsupporting
confidence: 86%
“…Decreasing the cutoff to > 3 WBC/HPF increased sensitivity but still resulted in an increased number of bacteremic UTI patients with negative test results. Reflex microscopic testing after a positive dipstick test result is still a common practice [ 17 ], but our results support others who have stopped reflex microscopic examination in outpatients [ 18 , 19 ] and inpatients [ 19 ] only done by physician request. On the other hand, there might be a role for microscopic examination in those with a negative dipstick in order to increase sensitivity.…”
Section: Discussionsupporting
confidence: 86%
“…The studies that reported data included collectively 4111 physicians and 175 563 patients (2 studies did not report the number of physicians, 34,35 and 8 studies did not report the number of patients, 20,22,23,28 30,32 34,35 and those numbers were also not available in related papers). There were 20 studies 36 55 in which outcomes for family physicians were not separable from those of other professional groups, and these were excluded from this review.…”
Section: Resultsmentioning
confidence: 99%
“…With all but one purely educational interventions having a time horizon of < 1 year there is no evidence in our review that educational strategies have long-term sustainability. In contrast there are several examples of system-based interventions which by definition require few resources to maintain, that are shown to maintain their effect for > 1 year [14,47,53]. The ratio of resource input to test reduction is not measured in the included studies but is an important consideration when deciding to implement a particular intervention.…”
Section: Sustainabilitymentioning
confidence: 99%